Analisis Data Satelit Altimetri Dalam Pemantauan Gelombang Laut di Perairan Provinsi Bengkulu - Yarmanto, Risky Budi; Irkhos, Irkhos; Suhendra, Suhendra; Lizalidiawati, Lizalidiawati (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Bengkulu Province, located on the west coast of Sumatra Island and facing directly onto the Indian Ocean, causes sea waves in Bengkulu Waters to be directly influenced by its geographical conditions. Sea waves in Bengkulu Waters vary due to the influence of monsoon winds and global climate. Seasonal variations in significant wave height (SWH) obtained from altimetry satellite imagery in five regions representing Bengkulu, namely Mukomuko Waters, North Bengkulu, Bengkulu City, Seluma, and Kaur can be used to monitor sea waves. The coordinates of the five regions representing Bengkulu Waters are as follows: Mukomuko is located at 2°40'20.82" S, 100°38'47.12" E; North Bengkulu at 3°20'6.55" S, 101°4'59.68" E; Bengkulu City is located at 4°0'7.57" S, 101°31'49.10" E; Seluma is located at 4°20'0.00"S, 102° 0'0.00"E; and Kaur is located at 5°0'59.65"S, 102°49'24.50"E. The data used for five years (2018-2022) is in the form of an average daily SWH every 3 hours and is processed using Panoply software to display the distribution of SWH and time series for each of the five regions in Bengkulu Waters. The results of the study show that the highest sea waves occurred in Kaur Waters, reaching 3.9 meters in August 2022 with an average wave height of 1.73 meters. Meanwhile, the lowest sea wave height occurred in Mukomuko Waters which reached 2.7 meters in January and February 2022, with an average wave height of 0.3 meters. Sea wave height in Mukomuko Waters, North Bengkulu Waters, Bengkulu City Waters, Seluma Waters, and Kaur Waters showed an increasing trend over the past five years. The relationship between significant wave height and season shows a consistent pattern.